S84 Idiopathic pulmonary fibrosis, asbestosis, or asbestos-related UIP? Findings from the idiopathic pulmonary fibrosis job exposures study (IPFJES). (12th November 2019) - Reynolds, C; Sisodia, R; Barber, C; Cullinan, P
Abstract : Introduction and objectives: Idiopathic pulmonary fibrosis (IPF) should not be diagnosed in the presence of an identifiable cause. Asbestos is fibrogenic and can cause usual interstitial pneumonia. Occupational asbestos exposure is common in the UK in the population at risk of developing IPF (mostly men in their 70s who have worked in manual occupations). Establishing occupational asbestos exposure in a particular individual, and determining whether or not to attribute causation, is difficult. Our aim was to characterize asbestos exposure in IPF with a view to informing diagnosis. Methods: Asbestos exposure was assessed using a job exposure matrix (JEM) based on occupational proportional mortality data for pleural mesothelioma and by means of a validated asbestos exposure reconstruction method for 856 participants (488 cases, 368 controls) from a UK based multicentre hospital-based case-control study, the idiopathic pulmonary fibrosis job exposures study (IPFJES). Results: 65% of cases and 63% of controls ever had a high or medium risk (for asbestos exposure) job. Cases spent an average of 24 years (std 17.6, median 21 years) in a high or medium risk job (std 17.1, median 27 years) and controls spent an average of 26 years (std 17.1, median 27 years). 25% of cases and 26% of controls recalled occupational asbestos exposure in sufficient detail to allow exposure reconstruction; mean estimated asbestos exposure was 1129 fibre ml years for cases (std 5663, median 7 fibre ml years) and 586 fibre ml years (std 3194, median 4 fibre ml years) for controls. Conclusions: Occupational asbestos exposure is common in patients with IPF and asbestosis is under-diagnosed. Overall, occupational asbestos exposure is not markedly different between patients with IPF and hospital controls; there does not appear to be a clear dose-response relationship or threshold effect.